A Comprehensive Toolbox for Genome Editing in Cultured Drosophila melanogaster Cells - Kunzelmann, Stefan (G3 (Bethesda), 2016)
Custom genome editing has become an essential element of molecular biology. In particular, the generation of fusion constructs with epitope tags or fluorescent proteins at the genomic locus facilitates the analysis of protein expression, localization, and interaction partners at physiologic levels. Following up on our initial publication, we now describe a considerably simplified, more efficient, and readily scalable experimental workflow for PCR-based genome editing in cultured Drosophila melanogaster cells. Our analysis at the act5C locus suggests that PCR-based homology arms of 60 bp are sufficient to reach targeting efficiencies of up to 80% after selection; extension to 80 bp (PCR) or 500 bp (targeting vector) did not further improve the yield. We have expanded our targeting system to N-terminal epitope tags; this also allows the generation of cell populations with heterologous expression control of the tagged locus via the copper-inducible mtnDE promoter. We present detailed, quantitative data on editing efficiencies for several genomic loci that may serve as positive controls or benchmarks in other laboratories. While our first PCR-based editing approach offered only blasticidin-resistance for selection, we now introduce puromycin-resistance as a second, independent selection marker; it is thus possible to edit two loci (e.g., for coimmunoprecipitation) without marker removal. Finally, we describe a modified FLP recombinase expression plasmid that improves the efficiency of marker cassette FLP-out. In summary, our technique and reagents enable a flexible, robust, and cloning-free genome editing approach that can be parallelized for scale-up.